Perlindungan Hukum terhadap Bidan yang Melakukan Penyalahgunaan Wewenang Ditinjau dari Undang-Undang Nomor 4 Tahun 2019 tentang Kebidanan (Studi Kasus di PMB Bidan R Desa Cikumbueun, Pandeglang) - Suhelianah Suhelianah; Faridatul Fauziah; Mohamad Noor Fajar Al Arif Fitriana (Yustisia Tirtayasa, 2022)
This study aims to find out how the responsibility of legal protection for midwives if they commit unlawful acts (Onrochmati gedaad) because of accidentally helping patients is connected with Law No. 28 of 2017. As a case in point: Mrs. R aged 35 years pregnant with the second, after delivery must immediately be carried out manual placenta action by the midwife, but because it is blocked by authority, the midwife cannot do it, even though skillfully the midwife is able to carry out the action. Normative juridical legal research methods that use a case approach and a descriptive analytical state approach as well as a statutory approach used to review related legislation. The results of this study arrived at a conclusion that the legal protection given to midwives was due to inadvertently helping patients carried out according to SOPs but when taking actions occurred outside of human reason such as uterine tears associated with Law 28 of 2017 article 23, then given the authority to provide services based on an assignment from the government as needed as referred to in Article 22 letter a, namely point b of authority because there are no other health workers in the area where the Midwife is on duty